Impact of salvage regimens on response and overall survival in acute myeloid leukemia with induction failure - Wattad, Mohammad Amen; Benner, Axel; Schlenk, Richard Friedrich (Leukemia, 2017)
We evaluated the impact of salvage regimens and allogeneic hematopoietic cell transplantation (allo-HCT) in acute myeloid leukemia (AML) with induction failure. Between 1993 and 2009, 3324 patients with newly diagnosed AML were enrolled in 5 prospective treatment trials of the German-Austrian AML Study Group. After first induction therapy with idarubicin, cytarabine and etoposide (ICE), 845 patients had refractory disease. In addition, 180 patients, although responding to first induction, relapsed after second induction therapy. Of the 1025 patients with induction failure, 875 (median age 55 years) received intensive salvage therapy: 7+3-based (n=59), high-dose cytarabine combined with mitoxantrone (HAM; n=150), with all-trans retinoic acid (A; A-HAM) (n=247), with gemtuzumab ozogamicin and A (GO; GO-A-HAM) (n=140), other intensive regimens (n=165), experimental treatment (n=27) and direct allo-HCT (n=87). In patients receiving intensive salvage chemotherapy (n=761), response (complete remission/complete remission with incomplete hematological recovery (CR/CRi)) was associated with GO-A-HAM treatment (odds ratio (OR), 1.93; P=0.002), high-risk cytogenetics (OR, 0.62; P=0.006) and age (OR for a 10-year difference, 0.75; P<0.0001). Better survival probabilities were seen in an extended Cox regression model with time-dependent covariables in patients responding to salvage therapy (P<0.0001) and having the possibility to perform an allo-HCT (P<0.0001). FLT3 internal tandem duplication, mutated IDH1 and adverse cytogenetics were unfavorable factors for survival.